2023
DOI: 10.1007/s43545-022-00588-1
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of how the disruption of mainstream schooling during the COVID-19 crisis provided opportunities that we can learn from so that we may improve our future relationship with the more-than-human world

Abstract: The COVID-19 crisis forced educators globally to reassess delivery of their curricula and educational priorities. Already the worsening climate crisis amid human beings’ deleterious relationship with the more-than-human world has caused many educators to demand radical reconsiderations as to the purpose and meaning of education. We ask: how did the disruption of mainstream schooling, during the COVID-19 crisis, provide opportunities that we can learn from so that we may improve our future relationship with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…These capabilities have always been important, of course, but recent challenges like automation of lower order tasks, globalization of the workforce, rising mental health issues, climate change and mass migration make them particularly relevant to this century ( Lambert, 2017 ). The emerging economic, educational and social ripples of the COVID-19 pandemic can be added to this list of 21st Century challenges ( Pendergast, 2022 ; Mann et al, 2022a ; Adams and Gray, 2023 ). Anderson and Jefferson (2018) suggested that “the skills which equip young people to engage with the world of work are the same skills that will help them live life to the full as 21st Century citizens” (p. 14).…”
Section: Introductionmentioning
confidence: 99%
“…These capabilities have always been important, of course, but recent challenges like automation of lower order tasks, globalization of the workforce, rising mental health issues, climate change and mass migration make them particularly relevant to this century ( Lambert, 2017 ). The emerging economic, educational and social ripples of the COVID-19 pandemic can be added to this list of 21st Century challenges ( Pendergast, 2022 ; Mann et al, 2022a ; Adams and Gray, 2023 ). Anderson and Jefferson (2018) suggested that “the skills which equip young people to engage with the world of work are the same skills that will help them live life to the full as 21st Century citizens” (p. 14).…”
Section: Introductionmentioning
confidence: 99%